PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA - Kholillah, Nur; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aimed to improve the skill of writing poetry students with the using of audiovisual media for grade V Elementary School 15 Pontianak Selatan. This method is using descriptive method with classroom action research form and collaborative research. Subjects of the study were 23 students. This study was conducted during III cycle with each cycle one time meeting.This results of the ability of teachers to plan learning from cycle I obtained an average value of 2.85, cycle II obtained an average value of 3.15,and cycle III obtained an average value of 3.64. The results of the ability of teachers to implement learning from cycle I obtained an average value of 2.94, cycle II obtained an average value of 3.27, and cycle III obtained an average value of 3.51. The percentage score of research writing poetry of students from cycle I that is 68,78%, cycle II that is 73,17%, and cycle III that is 78,96. So, using of audiovisual media can improve the skill of writing poetry students. Keywords: audiovisual media, improve, writing poetry skill